The Effect of Addition Super Red Dragon Fruit (Hylocereus Costaricensis) Peels Concentrate to Physico Chemical and Microstucture by SEM of Chicken Saussage - Dita Eka Oktaviningsih; Lilik Eka Radiati; Firman Jaya (Research Journal of Life Science, 2015)
The purpose of this reasearch was to determine SRDF (Super Red Dragon Fruit) peel concentrate added on Physico-chemical quality and Microstucture by SEM (Scanning Electron Microscope) of chicken sausages. The method research was experimental and designed using completely randomized design (CRD), which consists of 5 treatments and 5 replications. The treatments were T0: Chicken Sausage +  0% of SRDF peels concentrate (control), T1: Chicken Sausage +  5% SRDF peels concentrate,  T2: Chicken Sausage +  10% of SRDF peels concentrate, T3: Chicken Sausage +  15% of SRDF peels concentrate, T4: Chicken Sausage +  20% of SRDF peels concentrate. The variables measured were moisture content, fat content, color measure L*a*b*, texture and microstructure. Data were analyzed using one-way Anova, if there were a significant effect between the treatments then continued with Duncan’s Multiple Range Test. The addition 20% of SRDF peels concentrate on chicken sausage could decreasing color L* 43.56± 1.30, increasing the color a* 33.78± 2.36, decreasing color b* 12.96±0.48, decreasing fat content 40.87 ± 0.68, decreasing texture 3.16± 0.35, and increasing moisture 44.75 ± 8.7.